RETRACTED: Molecular structure and target recognition of neuronal calcium sensor proteins - Ames, James; Lim, Sunghyuk; Ikura, Mitsuhiko (Frontiers in Molecular Neuroscience, 2012)
Neuronal calcium sensor (NCS) proteins, a sub-branch of the calmodulin superfamily, are expressed in the brain and retina where they transduce calcium signals and are genetically linked to degenerative diseases. The amino acid sequences of NCS proteins are highly conserved but their physiological functions are quite distinct. Retinal recoverin and guanylate cyclase activating proteins (GCAPs) both serve as calcium sensors in retinal rod cells, neuronal frequenin (NCS1) modulates synaptic activity and neuronal secretion, K+ channel interacting proteins (KChIPs) regulate ion channels to control neuronal excitability, and DREAM (KChIP3) is a transcriptional repressor that regulates neuronal gene expression. Here we review the molecular structures of myristoylated forms of NCS1, recoverin, and GCAP1 that all look very different, suggesting that the sequestered myristoyl group helps to refold these highly homologous proteins into very different structures. The molecular structure of NCS target complexes have been solved for recoverin bound to rhodopsin kinase, NCS-1 bound to phosphatidylinositol 4-kinase, and KChIP1 bound to A-type K+ channels. We propose that N-terminal myristoylation is critical for shaping each NCS family member into a different structure, which upon Ca2+-induced extrusion of the myristoyl group exposes a unique set of previously masked residues that interact with a particular physiological target.